Inter-Group Face Recognition Bias Was Modulated by the Group Status - Hu, Bingjie; Yan, Linlin; Zheng, Chengyan; Tang, Yuhao; Lin, Qiuye; Xia, Wenling; Wang, Zhe (Frontiers in Psychology, 2022)
Previous studies showed that social categorization can induce an own-group face recognition bias. However, similar and better other-group face recognition emerged recently. In the present research, we aimed to examine whether competitive cues and group status accompanied by social categorization can modulate the inter-group face recognition bias. Moreover, we investigated how the group identification of individuals with different statuses affected the inter-group face recognition bias. The results indicated that an own-group face recognition bias emerged for targets with in-group labels compared to out-group labels. Moreover, when the group labels signaled competitive cues, the own-group face recognition bias was reversed. Furthermore, low-status and similar-status individuals exhibited out-group face recognition bias, but high-status individuals did not. Additionally, the higher the in-group identification scores of participants from the low-status group, the stronger the out-group face recognition bias. These results suggested that competitive cues would reverse the own-group face recognition bias and the group status would play a modulating role in face recognition bias.